Surgical Management of Juvenile Idiopathic Arthritis Related Dentofacial Deformities. Issue 1 (March 2022) - Wilson, Walter H.; Waite, Peter D.; Alrajhi, Zeyad; Powell, Kathlyn; Cron, Randy Q.; Kinard, Brian
Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatologic disease of childhood and frequently affects the temporomandibular joints (TMJ). JIA TMJ management requires a team approach. Initially, TMJ JIA involvement is managed with systemic therapy or intra-articular medications to treat symptoms and limit the growth deformity, however may later require surgical intervention. This case series describes 4 patients with different presentations and treatments of juvenile idiopathic arthritis affecting the temporomandibular joints to illustrate a proposed treatment algorithm. This algorithm is not designed to be an absolute treatment regimen but a framework to help clarify the presenting problems and interventions that may be considered to treat JIA associated temporomandibular dysfunction and dentofacial deformity. This case series represents the variety of JIA temporomandibular joint disease and offers a graduated appropriate treatment algorithm.